Innovation of Educational Table Game Tools in Stimulating Developmental Aspects of Early Childhood - Malpaleni Satriana; Ayu Aprilia Pangestu Putri; Yeni Solfiah; Sri Tatminingsih; Antung Dewi Nurliana Sagita; Diva Shally Mayumi; Rina Pujiati Pertiwi (Universitas Pendidikan Ganesha, 2024)
Learning innovation is needed to overcome various challenges in the world of education, particularly in efforts to improve the quality of stimulation for early childhood development. This study aims to develop and evaluate the effectiveness of an educational game tool in the form of an educational table called “My Development Aspects” as a stimulation medium that supports six aspects of child development. This study is a research and development (R&D) study that adopts the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The limited trial subjects involved early childhood children and teachers as the primary users of the medium. Data collection techniques were conducted through observation, interviews, and expert validation questionnaires, using instruments that had been tested for validity and reliability. Data were analyzed using descriptive qualitative and quantitative methods. The results of the study indicate that this educational table is designed with several activities on each side of the table, which is flexible for use indoors or outdoors, can be played individually or in groups, and allows for the replacement of materials according to the learning theme. This media is considered effective and efficient in supporting the stimulation of six aspects of child development, namely religious and moral values, physical motor skills, cognitive skills, language skills, social-emotional skills, and artistic skills. The conclusion of this study indicates that the “Aspek Perkembanganku” educational table has significant potential as an adaptive and applicable learning media innovation for early childhood educators.